MAKNA DAN BUDAYA MASYARAKAT BERAU DALAM PROSESI PINANGAN (Kajian Etnolinguistik) - Tialani, Karyani Tri; Indriyawati, Lilyn; Mulawarman, Widyatmike Gede (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
In this study, ethnolinguistics investigates the relationship between the pantun language and the Berau people or people who do not yet have writing. Pantun is one of Indonesia's cultural heritages and is a unique identity for its people. Pantun is part of the nature of Indonesian people's lives which of course can be used as learning. This qualitative descriptive research aims to describe and explore the Berau language rhymes used in courtship. The ethnolinguistic approach is supported by socio-cultural values in the form of linguistic and life characteristics which are reflected in words, signs or symbols. Therefore, ethnolinguistics plays an important role in this research, not only in determining and relating the use of language and the meaning of the pantun itself, but also in understanding the culture. This research obtains the results of examining the language of the text in the rhymes and explaining the Berau language rhymes in the Banua Adat Pinangan/Balamaran with strings of words that have aspects of cultural, religious and social values. The Banua (Berau) traditional proposal/Balamaran has a sacred meaning, especially in the verses of the Berau language pantun as a literary work of high artistic value. The symbolic values contained in the pantun are religious values, customary customs, ethical/moral values, and social values. In traditional ceremonies, rhymes of advice are usually included in talks or conversations.